The Influence of Work-Life Balance, Organizational Commitment, and Financial Stress on Turnover Intention Among Retail Employees in Cirebon City - Salsabila Puspa Mawangi; Edy Hartono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the impact of work-life balance, organizational commitment, and financial stress on turnover intention among retail employees, specifically focusing on the workforce at Surya Toserba in Cirebon City. High turnover intention in the retail sector has become a hidden crisis, driven by irregular working hours, weak emotional attachment to the company, and increasing economic pressures. Utilizing a quantitative associative approach, data were collected from 100 respondents using a simple random sampling technique. The analytical tool utilized in this research was multiple linear regression operated through SPSS software. The findings reveal that work-life balance and organizational commitment exert a significant and negative influence on turnover intention, acting as crucial mooring factors that retain employees. Conversely, financial stress demonstrates a significant and positive effect, serving as a strong push factor for employees to seek alternative employment. Simultaneously, the three independent variables significantly explain 83.4% of the variance in turnover intention. The study highlights that preventing employee turnover in the retail industry requires a holistic human resource strategy that accommodates flexible scheduling, fosters emotional attachment, and provides financial welfare support.